ตัวแบบสนับสนุนการตัดสินใจสำหรับการประเมินผลการปฏิบัติงานของบุคลากรมหาวิทยาลัยด้วยกระบวนการวิเคราะห์ตามลำดับชั้น - Hiranpongsin, Supawadee; Mahadilokrat, Kuntara; Ditcharoen, Nadh (วารสารหน่วยวิจัยวิทยาศาสตร์ เทคโนโลยี และสิ่งแวดล้อมเพื่อการเรียนรู้ (Journal of Research Unit on Science, Technology and Environment for Learning), 2021)
A Decision Support Model for the University Personnel Performance Assessment Using the Analytic Hierarchy Process Supawadee Hiranpongsin, Kuntara Mahadilokrat and Nadh Ditcharoen รับบทความ: 14 ตุลาคม 2563; แก้ไขบทความ: 26 ธันวาคม 2563; ยอมรับตีพิมพ์: 5 มกราคม 2564; ตีพิมพ์ออนไลน์: 4 มิถุนายน 2564 บทคัดย่อ งานวิจัยนี้มีวัตถุประสงค์เพื่อพัฒนาตัวแบบสนับสนุนการตัดสินใจสำหรับการประเมินผลการปฏิบัติงานของบุคลากรมหาวิทยาลัย โดยใช้แนวคิดของกระบวนการวิเคราะห์ตามลำดับชั้นในการให้ค่าน้ำหนักของเกณฑ์เพื่อหาร้อยละความสำคัญของเกณฑ์แล้วจึงแปลงเป็นค่าคะแนน จากนั้นนำค่าคะแนนที่ได้ไปจัดระดับผลการปฏิบัติงานตามเกณฑ์ซึ่งมี 5 ระดับ ได้แก่ ดีเด่น ดีมาก ดี พอใช้ และปรับปรุง ข้อมูลที่ใช้ในการวิจัย คือ ผลการประเมินการปฏิบัติงานของบุคลากร คณะวิทยาศาสตร์ มหาวิทยาลัยอุบลราชธานี จำนวน 2 รอบการประเมิน ได้แก่ รอบประเมินที่ 2 ปีงบประมาณ 2560 และรอบประเมินที่ 1 ปีงบประมาณ 2561 ผลการพัฒนาตัวแบบที่นำเสนอ พบว่า ค่าสัดส่วนความสอดคล้องกันของเกณฑ์เป็นไปตามเงื่อนไขของกระบวนการวิเคราะห์ตามลำดับชั้น การประเมินประสิทธิภาพของตัวแบบที่นำเสนอ แบ่งเป็น 2 ส่วนคือ 1) ประสิทธิภาพในการสนับสนุนการตัดสินใจสำหรับการประเมินผลการปฏิบัติงานของบุคลากรมหาวิทยาลัย โดยคำนวณค่าร้อยละของผลการประเมินการปฏิบัติราชการจริง เทียบกับผลการประเมินการปฏิบัติราชการที่แนะนำด้วยตัวแบบที่นำเสนอ และ 2) คุณภาพของตัวแบบที่นำเสนอซึ่งประเมินจากค่าดัชนีความสอดคล้อง โดยผู้บริหารคณะ จำนวน 3 ท่าน ผลการวิจัย พบว่า ประสิทธิภาพในการสนับสนุนการตัดสินใจมีความสอดคล้องกัน คิดเป็นร้อยละเฉลี่ย 75.34 และผลการประเมินด้วยค่าดัชนีความสอดคล้องของผู้บริหารที่มีต่อตัวแบบที่นำเสนอ มีค่าเท่ากับ 0.77 ดังนั้น ตัวแบบที่นำเสนอจึงมีความน่าเชื่อถือ และสามารถนำไปใช้เพื่อสนับสนุนการตัดสินใจสำหรับการประเมินผลการปฏิบัติงานของบุคลากรมหาวิทยาลัยได้ คำสำคัญ: ตัวแบบสนับสนุนการตัดสินใจ การประเมินผลการปฏิบัติงานของบุคลากร กระบวนการวิเคราะห์ตามลำดับชั้น Abstract This research aimed to develop a decision support model for the university personnel performance assessment using the Analytic Hierarchy Process (AHP). The proposed model applied the concept of AHP to give a weight of each criterion for determining the important percentage of those criteria and then converting it to a score. Then, the score was taken to set the level of personnel performance according to the criteria with five levels, namely, Excellent, Very Good, Good, Fair, and Improvement. The data used in this research were the personnel performance assessments in the Faculty of Science, Ubon Ratchathani University which were the second round of assessment in the fiscal year 2017 and the first round of assessment in the fiscal year 2018. The results for developing the proposed model found that the consistency ratio was according to the conditions of AHP. The evaluation of the model’s performance was divided into model evaluation and expert evaluation. The former was the decision support performance for evaluating the university personnel performance by calculating the percentage of the actual performance appraisal results compared with the recommended results with the proposed model. The latter was the proposed model quality which is evaluated from the index of item–objective congruence (IOC) with three faculty executives. The research results revealed that the efficiency of decision support was 75.34 percentage on average and the evaluation results with IOC of executives towards the proposed model were 0.77. Therefore, the proposed model was reliable and can be used to support decisions for the university personnel performance assessment. Keywords: Decision support model, Personnel performance assessment, Analytic hierarchy process